The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1159/000318295
|View full text |Cite
|
Sign up to set email alerts
|

Do Primary Care Physicians Have Particular Difficulty Identifying Late-Life Depression? A Meta-Analysis Stratified by Age

Abstract: Background: There is long-standing concern regarding poor recognition of depression in primary care, especially in older people. Methods: Studies that examined the unassisted (clinical) ability of general practitioners (GPs; primary care physicians) to identify depression were divided into those of older adults, younger adults and mixed populations. Data were extracted by 3 reviewers independently and pooled using a Bayesian meta-analysis. Results: We identified 31 valid studies that examined both sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 148 publications
1
89
1
4
Order By: Relevance
“…35 Approximately 66% of depression is underdiagnosed in primary care settings while a meta-analysis stratified on age found that general practitioners were only able to correctly identify 47% of late life depression cases. 36,37 Removing the barriers to diagnosis and management of depression in clinical practice is important to the care of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…35 Approximately 66% of depression is underdiagnosed in primary care settings while a meta-analysis stratified on age found that general practitioners were only able to correctly identify 47% of late life depression cases. 36,37 Removing the barriers to diagnosis and management of depression in clinical practice is important to the care of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, general practitioners might lack the time and the training to properly identify and address mental health problems, especially in older adults (Mitchell, Rao, & Vaze, 2010), as well as normalising the occurrence of certain conditions, such as depression (Burroughs et al, 2006). The high prevalence of physical chronic conditions in this age group might also deter the clinician of focusing on psychological problems.…”
Section: Page 6 Of 16mentioning
confidence: 99%
“…Approximately 10% to 15% of the older population suffers from some form of depressive complaint (Kraaij, 2001). Based on a recent meta analysis (Mitchell, Rao, & Vaze, 2010), the point prevalence of depression in older adults was estimated at 13.2%. Because ageing is accompanied by an objective increase in negative life events, for example personal loss and physical deterioration (e.g.…”
Section: Subjective Well-being In Later Lifementioning
confidence: 99%